2021
DOI: 10.3389/fimmu.2021.656796
|View full text |Cite
|
Sign up to set email alerts
|

ANCA Testing in Clinical Practice: From Implementation to Quality Control and Harmonization

Abstract: Analyses for the presence of anti-neutrophil cytoplasmic antibodies (ANCA) are important in the diagnostic work-up of patients with small vessel vasculitis. Since current immuno-assays are predominantly designed for diagnosis of patients with ANCA-associated vasculitis (AAV), implementation in routine clinical practice, internal and external quality control, and harmonization are focused on this particular use. However, ANCA testing may also be relevant for monitoring therapy efficacy and for predicting a clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Double-positive AAV patients turned to be single-positive or negative for MPO-ANCA and PR3-ANCA during follow-up. It was reported that ANCA was considered to be a well-recognized diagnostic biomarker and the persistence of ANCA is related to the occurrence of relapse in the future [ 46 , 47 ]. However, it was controversial to use ANCA titers to predict disease activities and/or guide therapy [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Double-positive AAV patients turned to be single-positive or negative for MPO-ANCA and PR3-ANCA during follow-up. It was reported that ANCA was considered to be a well-recognized diagnostic biomarker and the persistence of ANCA is related to the occurrence of relapse in the future [ 46 , 47 ]. However, it was controversial to use ANCA titers to predict disease activities and/or guide therapy [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the respective commercial assay is no longer available. As also established for ANCA-associated vasculitis [ 24 , 25 ], predicting disease relapses by rises in autoantibody levels should take into account disease subtype, definitions of relapse and rise in autoantibody level, frequency of autoantibody measurements, and type of assay used. As for diagnostic application, also for follow-up purposes sufficiently large studies comparing different immuno-assays in the same patient cohort are lacking.…”
Section: Anti-dsdna Antibodies In Relation To Disease Activitymentioning
confidence: 99%
“…ANCAs have promising potential in the diagnostics process, assessing therapy efficacy and even predicting the disease onset and staging [98,99]. The prevailing evidence suggests focusing on ANCA-specific immunoassays development, due to their high sensitivity and specificity compared to results based on IIF.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%